ANALISIS PENGARUH KUALITAS PRODUK DAN STRATEGI PROMOSI TERHADAP KEPUASAN PELANGGAN PADA BISNIS KULINER KEBAB BABAH ANTHA MEDAN - Permana, Jaka (Mitra prima, 2024)
This study aims to assess the effect of product quality and promotional strategies on customer satisfaction in the Babah Antha Kebab Culinary in Medan. The type of research used in this research is descriptive quantitative research. The processed data is the result of distributing questionnaires to customers of Kebab Babah Antha Medan. The sampling method is non- probability sampling and the technique used in collecting respondents is accidental sampling technique. The data analysis technique used in this study is multiple linear regression. Based on the results of data analysis, it can be concluded that Product Quality and Promotional Strategy have a positive and significant effect on Customer Satisfaction in the Kebab Babah Antha culinary business in the city of Medan. In this study, it was found that the value of product quality was 10.090 > ttable 1.988 with a significance level of 0.01 <0.05 so it can be concluded that product quality has a positive significant effect on customer satisfaction. Then the promotion strategy has a tcount of 5.099 > ttable 1.988 with a significance level of 0.01 <0.05 so it can be concluded that the promotion strategy has a positive significant effect on customer satisfaction. In addition, it also produces a Fcount value of 310.56 > Ftable 3.89 with a significance level of 0.01 < 0.05 so it can be concluded that in this study simultaneously product quality and promotion strategy have a significant effect on customer satisfaction.